Sustainability and challenges in hydrogen production: An advanced bibliometric analysis. (12th March 2023) - Catumba, Batista Dala; Sales, Misael Bessa; Borges, Pedro Tavares; Ribeiro Filho, Manoel Nazareno; Lopes, Ada Amélia Sanders; Sousa Rios, Maria Alexsandra de; Desai, Ajay S.; Bilal, Muhammad; Santos, José Cleiton Sousa dos
Abstract: Hydrogen has a high and diversified amount of feedstocks, methods, and improvement processes for its production. In recent years, studies on hydrogen production have been growing and diversifying to a greater extent. Hydrogen production can be based on renewable feedstocks such as biomass or fossil fuels such as petroleum. An analysis of 10, 655 publications from the Web of Science Core Collection database (2010–2022) was performed using VOSviewer, CiteSpace and Microsoft excel. The top three organizations that had the highest number of publications in the field of hydrogen production included the Chinese Academy Of Sciences, Ontario Tech University and Xi An Jiaotong University. The journal with the largest number of publications is the International Journal Of Hydrogen Energy. In addition to organizations and journals, the most promising authors and literature in this field of research were analyzed. Through cluster analysis, it was found that two constant search fields were Photocatalytic hydrogen production and Fermentative hydrogen production. Future studies should focus on process design, continuous photo-hydrogen production and looping steam. This bibliometric study focused on illustrating the overview of hydrogen production research, conducting a systematic survey of current research, which could be used by industry professionals and researchers interested in this area. Graphical abstract: Image 1 Highlights: Research on hydrogen production is assessed via the bibliometric method. Presentation of the growing interest in research on hydrogen production. Microsoft Excell, VOSviewer, and CiteSpace are employed to analyze 10, 655 publications. Comprehensive research guidelines are given for hydrogen researchers and producers. Analysis of the most used and least used raw material for hydrogen production.